2021
DOI: 10.3390/metabo11030131
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Improves Drought Stress Tolerance in Plants by Affecting Root Morphology, Root Exudates, and Microbial Diversity

Abstract: Potassium (K) reduces the deleterious effects of drought stress on plants. However, this mitigation has been studied mainly in the aboveground plant pathways, while the effect of K on root-soil interactions in the underground part is still underexplored. Here, we conducted the experiments to investigate how K enhances plant resistance and tolerance to drought by controlling rhizosphere processes. Three culture methods (sand, water, and soil) evaluated two rapeseed cultivars’ root morphology, root exudates, soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 50 publications
(58 reference statements)
2
24
0
Order By: Relevance
“…K fertilizer in combination with straw returning could improve the soil available K content [4]. On the one hand, straw returning brings in a large amount of straw K into the farmland; on the other hand, the root secretion of crops and the humification in the process of residual straw rot would weaken the fixation of K + on the clay mineral, promoting transformation of slowly available K to water-soluble K and available K, and maintain a new dynamic balance of various soil K forms [51,52]. Notably, the soil EOC and DOC had significant differences between the straw incorporation and without straw.…”
Section: Effects Of Long-term Straw Returning and K Fertilizer On The Soil Propertiesmentioning
confidence: 99%
“…K fertilizer in combination with straw returning could improve the soil available K content [4]. On the one hand, straw returning brings in a large amount of straw K into the farmland; on the other hand, the root secretion of crops and the humification in the process of residual straw rot would weaken the fixation of K + on the clay mineral, promoting transformation of slowly available K to water-soluble K and available K, and maintain a new dynamic balance of various soil K forms [51,52]. Notably, the soil EOC and DOC had significant differences between the straw incorporation and without straw.…”
Section: Effects Of Long-term Straw Returning and K Fertilizer On The Soil Propertiesmentioning
confidence: 99%
“…Drought is the most important one of abiotic stress factors that negatively influence the growth and production of various field crops [ 6 – 10 ]. Drought causes various changes in crop plants through different morphological, physiological, and biochemical responses [ 11 – 13 ]. Many studies have reported that the defense system of antioxidant was increased through the synthesis of antioxidants such as ascorbate peroxidase (APX) and glutathione reductase (GR), and enzymatic antioxidants such as peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD), which were stimulated to quench the ROS production in plants during drought stress [ 3 , 6 , 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ragot et al (2016) found that pH, organic carbon, and total nitrogen are important determinants responsible for the changes in phoD community structure at different P of grassland soil. Some studies reported that the application of K fertilizer can significantly alter the structure of soil microbial community, and available K is one of the key factors closely related to alterations in the composition of microbial community (Li et al, 2021;Xu et al, 2021). Wang et al (2020) also observed that some soil factors including total K, organic carbon, total N, and available P played key roles in shaping the soil phoD microbial community.…”
Section: Phod-and Gcd-harboring Microbial Diversities and Community S...mentioning
confidence: 99%